Raising Employee Cybersecurity Awareness Through Octalysis-Based Gamification: A Pre-Post Assessment Using HAIS-Q at the Ministry of Public Works and Public Housing - Ramadhan Papua Putra; Abba Suganda Girsang (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Rapid digital transformation has increased cybersecurity threats, while employee awareness remains a critical vulnerability in many organizations, including government institutions. Strengthening cybersecurity awareness is essential to reduce human-related security risks. Objective: This study aims to assess employee cybersecurity awareness at the Ministry of Public Works and Housing (Kementerian Pekerjaan Umum dan Perumahan Rakyat [Ministry of PUPR]) using the Human Aspects of Information Security Questionnaire (HAIS-Q) and to evaluate the effectiveness of an Octalysis-based gamification intervention in improving awareness across knowledge, attitude, and behavior dimensions. Methods: A pre-post quasi-experimental design was applied involving 146 employees. Data were collected using the validated HAIS-Q instrument before and after a four-week web-based gamification intervention. The gamification design implemented two Octalysis core drives: Development & Accomplishment and Empowerment of Creativity & Feedback, through leaderboard, badge, and instant feedback features. Results: The findings show that overall cybersecurity awareness increased from 75.85% (medium level) to 83.69% (good level), indicating a 10.33% improvement. All seven HAIS-Q focus areas improved, with the most significant gain observed in internet use (58.22% to 69.79%). Conclusion: The Octalysis-based gamification approach effectively enhanced employee cybersecurity awareness. Integrating gamification with HAIS-Q provides a structured and evidence-based method for improving cybersecurity behavior in government organizations.